Catastrophising and repetitive negative thinking tendencies in patients with psychogenic non-epileptic seizures or epilepsy. (December 2020) - Whitfield, Andrew; Walsh, Sean; Levita, Liat; Reuber, Markus
Highlights: Catastrophising and repetitive negative thinking (RNT) was higher in patients with psychogenic non-epileptic seizures (PNES) than epilepsy. The PNES diagnosis contributed to RNT independently of depression and anxiety levels. Catastrophising and RNT may be cognitive manifestations of chronic high arousal. Chronic high arousal may decrease inhibitory processes and facilitate PNES. RNT and catastrophisation are potential specific targets in psychotherapy for PNES. Abstract: Purpose: Previous research suggests that catastrophisation and perseverative, or repetitive negative thinking (RNT) could play an important role in the aetiology of Psychogenic Nonepileptic Seizures (PNES). This study was designed to explore whether these cognitive tendencies are more prevalent in patients with PNES than those with epilepsy and to examine the relationship between these cognitions, depression, anxiety, seizure frequency and diagnosis. Methods: 26 patients with PNES (PWPNES) and 29 with epilepsy (PWE) self-reported RNT (Perseverative Thinking Questionnaire), catastrophisation tendencies (modified Safety Behaviors and Catastrophizing Scale), symptoms of anxiety (Generalised Anxiety Disorder Assessment 7) and depression (Primary Health Questionnaire 9) as well as seizure frequency. Results: RNT and catastrophic thinking were highly correlated with each other and more prevalent in PWPNES than PWE. Positive correlations were also found between all other self-report measures and seizure frequency. The PNES diagnosis predicted RNT (perseverative thinking) independently of catastrophic thinking, anxiety, depression and seizure frequency. Conclusion: PWPNES exhibit greater negative perseverative and catastrophising cognitive tendencies than PWE. PNES as a diagnosis independently predicted RNT. Hence, RNT and catastrophisation should be considered as possible specific targets for psychological interventions in patients with PNES.